Numerical Cohesive Zone Modeling (CZM) of Self-Anchoring AM Metal-CFRP joints (Fracture and Structural Integrity, 2024)
The escalating importance of lightweight design in engineering demands innovative strategies to tackle this challenge. Traditionally, the joining of these materials involves rivets, bolts, or adhesives. However, contemporary manufacturing techniques, such as 3D printing, present the potential to fabricate joints without the necessity for additional binding mechanisms. This paper delves into a promising initiative concerning the joining of multimaterial systems, specifically composites and metals. The fabrication of the metal component of the joint through additive manufacturing (AM) enables the manipulation of surface geometry by incorporating patterned anchors. This, in turn, facilitates the direct co-curing of the composite onto the modified metallic surface. The primary objective is to enhance mechanical interlocking without relying on traditional fastening elements or adhesives. The study evaluates various anchor geometries to assess their efficacy in increasing the overall joint strength. This assessment employs the cohesive zone modeling (CZM) method to simulate joint specimens, followed by comparative analyses to quantify the strengths of the joints.
Keywords: Single-lap joints; additive manufacturing; composites; multimaterial joining; cohesive zone modelling; adhesives